Irrigation management for diversified crops: Opportunities for learning and improvement - Valera, A.; Cablayan, D.; Elegado, J. (1989)
The interim results of the study as conducted by the International Irrigation Management Institute (IIMI) is presented. Existing practices of farmers and the National Irrigation Administration (NIA) personnel in managing the available water supply are highlighted. These practices were analyzed for possible adoption in other NIA systems. The paper also presents opportunities for improvements to optimize land and water use during the dry season.